High Efficiency Graphene Coated Copper Based Thermocells Connected in Series - Sindhuja, Mani; Indubala, Emayavaramban; Sudha, Venkatachalam; Harinipriya, Seshadri (Frontiers in Physics, 2018)
Conversion of low-grade waste heat into electricity had been studied employing single thermocell or flowcells so far. Graphene coated copper electrodes based thermocells connected in series displayed relatively high efficiency of thermal energy harvesting. The maximum power output of 49.2W/m2 for normalized cross sectional electrode area is obtained at 60ºC of inter electrode temperature difference. The relative carnot efficiency of 20.2% is obtained from the device. The importance of reducing the mass transfer and ion transfer resistance to improve the efficiency of the device is demonstrated. Degradation studies confirmed mild oxidation of copper foil due to corrosion caused by the electrolyte.